2000
DOI: 10.1093/jac/46.3.391
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic resistance of Mycobacterium tuberculosis to clarithromycin is effectively reversed by subinhibitory concentrations of cell wall inhibitors

Abstract: Subinhibitory concentrations of bacitracin, vancomycin and other inhibitors of cell wall synthesis reversed to varying extents the intrinsic resistance of Mycobacterium tuberculosis to clarithromycin. Ethambutol reversed clarithromycin resistance in all of the M. tuberculosis strains studied regardless of their susceptibility to this drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 34 publications
1
24
0
1
Order By: Relevance
“…Most studies performed drug susceptibility testing against M. tuberculosis by determining the MIC using the radiometric BACTEC 460 method [36][37][38][39][40][41][44][45][46]. Often a concentration range up to 16 μg·mL −1 was used [36,37,39,41].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies performed drug susceptibility testing against M. tuberculosis by determining the MIC using the radiometric BACTEC 460 method [36][37][38][39][40][41][44][45][46]. Often a concentration range up to 16 μg·mL −1 was used [36,37,39,41].…”
Section: Resultsmentioning
confidence: 99%
“…Often a concentration range up to 16 μg·mL −1 was used [36,37,39,41]. Overall, studies have shown no susceptibility of MDR-TB strains to CLR, with all studies reporting high MIC values [36][37][38][39][40][41]. This was also observed for roxithromycin, azithromycin (AZI) [41] and the metabolite of CLR 14-hydroxyclarithromycin [36].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations